Training modalities for elder sarcopenic obesity: a systematic review and network meta-analysis - Qiu, Hao; Zheng, Wanxia; Zhou, Xi; Liu, Qianrong; Zhao, Xuehong (Frontiers in Nutrition, 2025)
IntroductionSarcopenic obesity (SO) is a condition characterized by the coexistence of age-related obesity and sarcopenia. This systematic review and network meta-analysis (NMA) aimed to compare the effects of different training modalities, such as aerobic training (AT), resistance training (RT), combined resistance with AT (CT), and multicomponent training (MCT) on body composition, muscle strength, and physical performance in elderly patients with SO.MethodsWe electronically searched randomized controlled trials, published from inception to March 2024 in PubMed, Embase, Cochrane Library, Web of Science and Scopus. Effect estimates were presented as mean differences (MD) or Standard Mean Difference (SMD) with 95% confidence interval (CI). The comprehensive effects of all treatments were ranked by the surface under the cumulative ranking (SUCRA) probabilities.Results14 trials enrolling 955 participants were included. The body fat percentage (BFP) in MCT (MD= −6.37, 95% CI: −8.67, −4.07), CT (MD = −2.08, 95% CI: −4.00, −0.16), and RT (MD = −1.85, 95% CI: −3.25, −0.44) was significantly lower than in the normal control group, with MCT showing superior effects compared to CT and RT. Furthermore, only MCT significantly improved fat-free mass (FFM; MD = 5.21, 95% CI:1.51, 8.91), as well as in body mass index (BMI; MD = 0.74, 95% CI:0.08, 1.40). In addition, handgrip strength (HGS) significantly improved under both MCT (SMD = 0.87, 95% CI: 0.19, 1.5) and RT(SMD = 0.84, 95% CI: 0.43, 1.25). The performance on the 30s chair stand test also yielded better outcomes for MCT (MD = 3.10, 95% CI: 1.33, 4 0.86), CT(MD = 2 0.50, 95% CI: 0.18, 5.18), and RT(MD = 3.91, 95% CI: 2.30, 5.52) when compared to the control group. Lastly, gait speed was enhanced by both MCT (MD = 0.35, 95% CI: 0.30, 0.41) and CT(MD = 0.14, 95% CI: 0.06, 0.21). The ranking results indicated that MCT was superior to other training modalities in enhancing body composition and gait speed. In contrast, RT appears to be more advantageous in the 30-second chair standing test and in improving HGS.ConclusionMCT outperformed other training modalities in improving body composition and gait speed. RT was more beneficial for the 30-second chair standing test and enhancing HGS. These findings provide valuable insights for clinicians and researchers to customize exercise prescriptions for older patients with SO.Systematic review registrationhttp://www.crd.york.ac.uk/PROSPERO/display_record.asp?ID=CRD42024544962.